HIGHER EDUCATION AND GENDER EQUALITY: CASE STUDY OF STATE UNIVERSITY STUDENTS IN INDONESIA - Yuspiani, Yuspiani; Naro, Wahyuddin; Goncing, Abdi (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
This study aims to investigate the relationship between higher education and gender equality among public university students in Indonesia. Based on the form of data and the nature of the observed object, this research is classified as a survey research. The results of this study show that despite the increase in women's participation in higher education in Indonesia, gender gaps still exist in various aspects of student life. Although there are policies and programs that support gender equality, their implementation is still limited and sometimes faced with cultural and social challenges. Education in gender perspective is the thought that education is organized for everyone without discriminating gender, ethnicity, and nation, and education is not discriminatory but will prioritize education for men and women which will ultimately facilitate gender equality in relations between men and women. This study points to the need for further efforts to improve gender equality in higher education. Policies and programs that focus on strengthening gender awareness, providing better academic and social support for female students, and addressing lingering gender norms and stereotypes in society are needed to create an inclusive and equal educational environment for all students. Higher education in Indonesia is still faced with the challenge of gender equality. Despite positive steps taken, greater efforts are needed to achieve true gender equality among public university students in Indonesia. Abstrak: Penelitian ini bertujuan untuk menyelidiki hubungan antara pendidikan tinggi dan kesetaraan gender di kalangan mahasiswa perguruan tinggi negeri di Indonesia. Berdasarkan bentuk data dan sifat objek yang diamati, penelitian ini diklasifikasikan sebagai penelitian survei. Hasil penelitian ini menunjukkan bahwa meskipun ada peningkatan partisipasi perempuan dalam pendidikan tinggi di Indonesia, kesenjangan gender masih ada di berbagai aspek kehidupan mahasiswa. Meskipun ada kebijakan dan program yang mendukung kesetaraan gender, implementasinya masih terbatas dan terkadang dihadapkan pada tantangan budaya dan sosial. Pendidikan dalam perspektif gender bahwa pendidikan diselenggarakan untuk semua orang tidak membeda-bedakan jenis kelamin, etnis dan bangsa dan pendidikan tidak diskriminatif tetapi akan memprioritaskan pendidikan bagi laki-laki dan perempuan yang pada akhirnya akan memfasilitasi kesetaraan gender dalam hubungan antara laki-laki dan perempuan. Studi ini menunjukkan perlunya upaya lebih lanjut untuk meningkatkan kesetaraan gender di pendidikan tinggi. Kebijakan dan program yang berfokus pada memperkuat kesadaran gender, memberikan dukungan akademik dan sosial yang lebih baik bagi mahasiswa perempuan, serta mengatasi norma dan stereotip gender yang masih ada di masyarakat, diperlukan untuk menciptakan lingkungan pendidikan yang inklusif dan setara bagi semua mahasiswa. Pendidikan tinggi di Indonesia masih dihadapkan pada tantangan kesetaraan gender. Meskipun ada langkah-langkah positif yang diambil, upaya yang lebih besar diperlukan untuk mencapai kesetaraan gender yang sebenarnya di kalangan mahasiswa perguruan tinggi negeri di Indonesia.